Characterization of a carboxyl methyltransferase in Fusarium graminearum provides insights into the biosynthesis of fusarin A. Issue 30 (1st July 2021) - Yang, Qian; Wang, Wanqiu; Lin, Yueting; Lin, Yuqi; Tang, Zhijun; Wang, Jing; Tao, Jiang; Tang, Weihua; Liu, Wen
Abstract : We report here an S -adenosyl methionine-dependent carboxyl methyltransferase responsible for the formation of the methyl ester moiety by biochemical characterization, which provide insights into the biosynthetic pathway of fusarin A. Abstract : Fusarium graminearum is a major fungal pathogen that causes a series of devastating crop diseases by producing a variety of mycotoxins. Fusarins are a class of polyketide-nonribosomal peptide hybrids. In Fusarium mycotoxins, a variable 2-pyrrolidone ring conjugates with a polyene chain substituted with a methyl ester moiety. The enzymatic route through which fusarin A, a major member of the fusarin family with a characteristic tetrohydrofuran-coupled pyrrolidone ring, is formed in F. graminearum has not been established. By targeting the final step in the biosynthesis of fusarin A, we report here an S -adenosyl methionine-dependent carboxyl methyltransferase responsible for the formation of the methyl ester moiety by in vivo gene inactivation, isolation and characterization of a key fusarin intermediate, and in vitro biochemical characterization. Related findings provide insights into the poorly understood biosynthetic pathway of fusarin A. Additionally, bioactivity assays demonstrate that the methyl ester is necessary for fusarin cytotoxicity.